The immunogenicity of plant-based COE-GCN4pII protein in pigs against the highly virulent porcine epidemic diarrhea virus strain from genotype 2 - Ho, Thuong Thi; Trinh, Vy Thai; Tran, Hanh Xuan; Le, Phuong Thu Thi; Nguyen, Tra Thi; Hoang, Hang Thu Thi; Pham, Minh Dinh; Conrad, Udo; Pham, Ngoc Bich; Chu, Ha Hoang (Frontiers in Veterinary Science, 2022)
Porcine epidemic diarrhea virus (PEDV) is a serious infectious causative agent in swine, especially in neonatal piglets. PEDV strains belonging to genotype 2 (G2) especially G2a were the major causative of Porcine epidemic diarrhea (PED) outbreaks in Vietnam. Here we produced a plant-based CO-26K-equivalent epitope (COE) variant from a Vietnamese highly virulent PEDV strain belonging to genotype 2a (COE/G2a) and evaluated the protective efficacy of COE/G2a-GCN4pII protein (COE/G2a-pII) in piglets against the highly virulent PEDV G2a strain following the passive immunity. Five-day-old piglets showed high levels of PEDV-specific IgG antibodies, COE-IgA specific antibodies, neutralizing antibodies, and IFN-γ responses. After virulent challenge experiments, all of these piglets survived and had normal clinical symptoms, no watery diarrhea in feces, and an increase in piglets' body weight while all negative control piglets died. These results suggest that the COE/G2a-pII protein produced in plants can be developed as a promising vaccine candidate to protect piglets against PEDV G2a infection in Vietnam.